Tuhan Ada di Mana-mana: Mencari Makna bagi Korban Bencana di Indonesia - Johannis Siahaya; Karel Martinus Siahaya; Nunuk Rinukti (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
The phenomenon of natural disasters has been felt in recent years and has become a global concern. This concern occurs because, the intensity of natural disasters that are increasingly frequent in various parts of the world lately, taking many victims both human, property, and other lives. Religions (including the church), however, have an essential calling and responsibility in dealing with the problem of the victims of the disaster. However, today's reality shows that religions (as well as internal church) are still involved and struggling in classical debates about teachings (dogma) about who God is: about his name, which God or religion is true, or what God teaches in which religion or church which is considered correct. Abstrak Fenomena bencana alam sangat terasa dalam beberapa tahun terakhir sampai-sampai menjadi perhatian dunia. Hal ini terjadi karena, intensitas benca-na alam yang semakin sering terjadi di berbagai belahan dunia termasuk di Indonesia akhir-akhir ini, bahkan mengakibatkan banyak korban yang berja-tuhan, selain kehilangan harta benda. Melihat fenomena ini gereja memiliki panggilan dan tanggung jawab yang hakiki dalam dalam menangani korban bencana tersebut. Namun, realitas yang terjadi adalah Agama-agama lain bahkan gereja masih saja terlibat dalam berbagai perdebatan mengenai siapa Tuhan itu, mengenai nama-Nya, Agama mana yang benar, ataupun ajaran Tuhan dari agama atau gereja mana yang dianggap benar.